Optimizing Ecotourism Management Strategies for Mangrove Forests: A Maqashid Sharia Approach in Batu Bara Regency - Husyairi, Mhd. Alwi Syam; Nawawi, Zuhrinal M (Universitas Muhammadiyah Jakarta, 2024)
Mangrove ecotourism was developed to promote the welfare of local communities by leveraging natural resources in a sustainable manner. This study investigated strategies to increase visitor numbers to Batu Bara Mangrove Park (BBMP) and improve the socio-economic conditions of the surrounding community. A descriptive mixed method was utilized, employing SWOT (Strength, Weakness, Opportunity, Threat) analysis to analyze data collected through interviews, observations, and questionnaires. The research sought to understand key factors contributing to the growth in visitor numbers while addressing challenges faced by park management. Additionally, the study included a welfare analysis based on the principles of Maqashid As-Syariah, which provided an Islamic perspective unique to this research. The findings identified various strategies that could be implemented to better meet visitor needs and preferences, enhancing the overall visitor experience. These strategies focused on improving facilities, services, and aligning development efforts with tourist expectations. By doing so, BBMP could establish itself as a more appealing and sustainable ecotourism destination. The study concluded that addressing visitor satisfaction through tailored development strategies not only holds the potential to increase tourism but also significantly contributes to the economic and social welfare of the local community. This research offers valuable insights into the sustainable management of ecotourism in similar regions.